Pedagogical perspectives on teaching English for pre-school children during Covid-19 pandemic: An ethnographic study - Irma Wahyuni; Syihabuddin Syihabuddin (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2022)
The Indonesian government had announced a large scale of social and physical distancing since the COVID-19 Pandemic occurred in Indonesia in March 2020. It leads to the restriction of educational institutions, particularly formal secondary and elementary schools. Teachers, parents, and students are encouraged to adapt well to the situation. The Indonesian government has released a new temporary learning policy during Pandemic for elementary school students, called the emergency curriculum. It urges elementary school students to learn at home through teacher supervision via online platforms. It is not simple to educate and teach children at home, mainly teaching English for parents busy with their jobs. By employing an ethnographic study in an early childhood education institution in Bogor, this research investigates the online learning and blended learning process during the COVID-19 Pandemic, specifically learning English. The advantages, challenges, and weaknesses of the English teaching-learning process will be explored and related. Recommendation for further studies and other learning management processes during Pandemic will be encouraged as the significance of the research.